Coronary artery plaque rupture and erosion: Role of wall shear stress profiling and biological patterns in acute coronary syndromes. (1st January 2023) - Russo, Giulio; Pedicino, Daniela; Chiastra, Claudio; Vinci, Ramona; Lodi Rizzini, Maurizio; Genuardi, Lorenzo; Sarraf, Mohammad; d'Aiello, Alessia; Bologna, Marco; Aurigemma, Cristina; Bonanni, Alice; Bellantoni, Antonio; et al.
Abstract: Aims: Wall shear stress (WSS) is involved in coronary artery plaque pathological mechanisms and modulation of gene expression. This study aims to provide a comprehensive haemodynamic and biological description of unstable (intact-fibrous-cap, IFC, and ruptured-fibrous-cap, RFC) and stable (chronic coronary syndrome, CCS) plaques and investigate any correlation between WSS and molecular pathways. Methods and results: We enrolled 24 CCS and 25 Non-ST Elevation Myocardial Infarction-ACS patients with IFC ( n = 11) and RFC ( n = 14) culprit lesions according to optical coherence tomography analysis. A real-time PCR primer array was performed on peripheral blood mononuclear cells for 17 different molecules whose expression is linked to WSS. Computational fluid dynamics simulations were performed in high-fidelity 3D-coronary artery anatomical models for three patients per group. A total of nine genes were significantly overexpressed in the unstable patients as compared to CCS patients, with no differences between IFC and RFC groups (GPX1, MMP1, MMP9, NOS3, PLA2G7, PI16, SOD1, TIMP1, and TFRC) while four displayed different levels between IFC and RFC groups (TNFα, ADAMTS13, EDN1, and LGALS8). A significantly higher WSS was observed in the RFC group ( p < 0.001) compared to the two other groups. A significant correlation was observed between TNFα (p < 0.001), EDN1 ( p = 0.036), and MMP9 ( p = 0.005) and WSS values in the RFC group. Conclusions: Our data demonstrate that IFC and RFC plaques are subject to different WSS conditions and gene expressions, suggesting that WSS profiling may play an essential role in the plaque instability characterization with relevant diagnostic and therapeutic implications in the era of precision medicine. Highlights: Wall shear stress (WSS) is involved in coronary artery plaque pathological mechanisms and modulation of gene expression. Different phenotypes of coronary artery plaques (intact fibrous cap and ruptured fibrous cap) are subject to different WSS and gene expression. The combination of fluid-dynamic with biological profiling might help to characterize coronary artery plaque and to detect unstable ones.